Pengaruh Electronic Word Of Mouth, Product Knowledge terhadap Keputusan pembelian Ramen dengan Halal Awareness sebagai Variabel Intervening - Suprapti, Isdiana -; Saputro, Dimas Bayu; Fauziyah, Elys -; Hasan, Fuad - (ITB AAS INDONESIA Surakarta, 2024)
Ramen is a traditional Japanese food that is favored by the Indonesian people despite the pros and cons regarding the halalness of the product. Ramen is a new menu at Mbokde Cemal-Cemil which causes an increase in consumers. The research was conducted with the aim of describing the characteristics of variables based on the results of field observations, analyzing the effect of electronic word of mouth, product knowledge, halal awareness directly and indirectly on ramen purchasing decisions. This study used 100 samples using the Coachran calculation and was selected purposively. The data analysis method is descriptive analysis and Partial Least Square (PLS) analysis. The results showed that electronic word of mouth, product knowledge, halal awareness directly had a significant influence on purchasing decisions. Electronic word of mouth through product knowledge on purchasing decisions has a significant effect, meaning that product knowledge can mediate electronic word of mouth on purchasing decisions.